Price modeling of the non-load bearing concrete hollow blocks (CHBs) manufactured in Ilocos Sur - Esguerra, Norma A. (Philippine Engineering Journal)
In this study, non-load bearing CHBs were bought as samples from sixteen (16) towns chosen at random from manufacturers, eight (8) of which were selected from the First District and another eight (8) from the Second District of Ilocos Sur. The findings are: the samples were smaller than the recommended standard; from the variables compared, only the thickness and strength parameters were significant in influencing the price of the commodity being studied; the strength of the samples were lower than the minimum specified strength of 2.07MPa; no significant difference between and among the sizes, strengths and distance of the quarry site from the place of production exist; CHBs are more frequently sold on delivery mode; and strength and price have significant relationship. A linear mathematical model, Y =3.836+0.748fc'+0.92t was developed to calculate the price of concrete hollow blocks resulting from a regression analysis, where: Y is the delivery price of the CHB, fc' is the compressive strength of the CHB produced, t is the thickness. In conclusion, CHB manufacturers set a uniform price for their products to be competitive, without considering the quarry site distance and strength. Only 41.1% of the variance were identified in this study. Future researches may explore the remaining 58.9% of the variance for a rational pricing of CHB products; adherence by manufacturers to the prescribed sizes and strength of CHBs and more strict monitoring by concerned agency to the identified concerns be addressed.